2020
DOI: 10.1016/j.jval.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of Discrete-Event Simulation in Health Technology Assessment: A Cost-Effectiveness Analysis of Alzheimer’s Disease Treatment Using Real-World Evidence in Thailand

Abstract: Objectives: Decision-analytic models for Alzheimer's disease (AD) have been advanced to a discrete-event simulation (DES), in which individual-level modeling of disease progression across continuous severity spectra become feasible. This study aimed to apply DES to perform cost-effectiveness analysis of AD treatment in Thailand.Methods: A data set of Thai AD patients, representing unique demographic and clinical characteristics, was bootstrapped to generate a baseline cohort of 50 000 patients. Each patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Eight studies (35%) were conducted in Europe [ 31 , 37 , 42 , 45 , 47 , 49 – 51 ], eight (35%) were conducted in the US [ 32 34 , 36 , 39 41 , 48 ], and two (9%) were conducted in Canada [ 44 , 46 ]. Additionally, single studies (4% each) were conducted in Australia [ 52 ], Brazil [ 30 ], South Korea [ 43 ], Taiwan [ 38 ], and Thailand [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies (35%) were conducted in Europe [ 31 , 37 , 42 , 45 , 47 , 49 – 51 ], eight (35%) were conducted in the US [ 32 34 , 36 , 39 41 , 48 ], and two (9%) were conducted in Canada [ 44 , 46 ]. Additionally, single studies (4% each) were conducted in Australia [ 52 ], Brazil [ 30 ], South Korea [ 43 ], Taiwan [ 38 ], and Thailand [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most of the included studies, analyses were performed using TreeAge [ 30 , 31 , 35 , 40 , 43 , 48 , 49 ] and Microsoft Excel [ 34 , 36 , 47 , 50 , 51 ] each with six studies (52%, in total). For a CBA conducted through decision tree modelling, a combination of Stata Standard Edition (SE) version v16 and TreeAge Pro 2019 software was used in the study [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD-ACE model applications (22, 34, 41) showed higher lecanemab treatment value with higher discontinuation rates, with maintained reduced amyloid level after stopping treatment and with lower dosing frequency while assuming no treatment effect waning, and lower lecanemab treatment value with shorter maximum treatment duration. Kongpakwattana et al (42) showed a higher cost-effectiveness ratio with earlier stopping donepezil at severe dementia. Ross et al (15) showed a higher cost-effectiveness ratio with later discontinuation at severe instead of moderate dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of simulation in healthcare vary in scope, including material flow planning in hospitals [24], COVID-19 RT-PCR testing processes [25], patient scheduling [26], patient registration processing [27], using virtual reality [28], and assessing health technology [29]. On the other hand, lean, SS, and LSS interventions (LSS) have also been implemented with different approaches and goals, e.g., redesigning a supply chain for an operating room [30], improving the discharge process [31], redesigning the scheduling process for elective surgery [32], enhancing the patient flow in emergency department (ED) [33], or improving controlled drug processes [34].…”
Section: Introductionmentioning
confidence: 99%